The Relationship of Ankylosing Spondylitis and Subclinical Atherosclerosis: A Systemic Review and Meta-Analysis. (July 2019) - Bai, Ruocen; Zhang, Yanfen; Liu, Wen; Ma, Chunyan; Chen, Xin; Yang, Jun; Sun, Dandan
Cardiovascular disease has become the first cause of death for patients with ankylosing spondylitis (AS). However, the relevant data is limited and the relationship between AS and subclinical atherosclerosis remains questionable. Therefore, we assessed the relationship between subclinical atherosclerosis and AS in this meta-analysis. We synthesized the primary data on flow-mediated vasodilation (FMD), carotid intima media thickness (cIMT), or pulse wave velocity (PWV)-related studies involving AS and using searched electronic databases. Not only were heterogeneity tests, publication bias, and sensitivity analysis performed overall, but also subgroup analysis and meta-regression grouped by measuring site, region, age, sex, and sample size were also carried out. A total of 35 articles involving 1535 patients with AS and 1347 normal controls were included. Significantly increased cIMT (weighted mean difference [WMD]; 95% confidence interval [CI]) = 0.071 [0.048-0.094]), PWV (WMD [95%CI] = 0.910 [0.464-1.356]), and decreased FMD (WMD [95%CI] = −4.459 [−8.389 to −0.529]) were observed in patients with AS compared to controls. The funnel plots or Egger test or Begg test showed no significant publication bias (all P > .05). Sensitivity analysis did not show statistical significance. We conclude that patients with AS have a higher risk of subclinical atherosclerosis. Early screening and intervention deserves consideration.